Notch Signaling Is Associated with Pulmonary Fibrosis in Patients with Pigeon Breeder’s Lung by Regulating Oxidative Stress - Zhichuang Lian; Remila Kuerban; Zongxin Niu; Paruzha Aisaiti; Chao Wu; Xiaohong Yang (Emergency Medicine International)
This study explored the molecular mechanism underlying the association of Notch signaling and oxidative stress with the occurrence of pulmonary fibrosis in patients with pigeon breeder’s lung (PBL). Rat models of fibrotic PBL were constructed with freeze-dried protein powder, and the animals were divided into the control (intratracheal instillation of normal saline; n = 9), M (PBL model; intratracheal instillation of freeze-dried protein powder; n = 9), and M + D (PBL+ the Notch inhibitor DAPT; n = 9) groups. Immunohistochemistry was employed to observe the protein levels of pathway factors and α-SMA, and the levels of ROS, GSH-PX, SOD, and MDA were observed using ELISA. To verify the results of the animal experiment, cytological models were constructed. The M group and the M + D group had significantly increased α-SMA levels (P<0.05). Although both groups had significantly higher key protein levels in the Notch channel, the M + D group had significantly lower levels relative to the M group (P<0.05). Oxidative stress products were examined, and the levels of MDA and ROS were significantly increased, while those of GSH-PX and SOD were significantly decreased in the M and M + D groups as compared to the control, but the M group and the M + D group significantly differed (P< 0.05). These findings were further validated by the cytological experiment. Notch signaling is associated with pulmonary fibrosis in PBL by regulating cellular oxidative stress, and inhibiting this pathway can slow down pulmonary fibrosis progression.